Collocations et représentation fémininedans les œuvres de Colette : Une analyse linguistique et littéraire - Golda, Paweł; Roemer, Julia (2023)
Sidonie-Gabrielle Colette played a significant role in the development of French literature. Her novels vividly depict independent and self-aware women, thereby reflecting the author herself. Colette's works have captured the attention of researchers and have been the subject of numerous studies. In this proposed research, an interdisciplinary approach combining literary and linguistic perspectives is adopted to explore Colette's literature. The objective of this study is to closely examine the portrayal and circumstances of women and girls in Colette's work, specifically focusing on the nomino-adjectival collocations involving the lexemes femme and fille used by the author in her six novels from the “Claudine” series. These novels serve as prime examples of Colette's reclamation of autonomy through her writing. The research will culminate in a literary analysis, contrasting the results obtained through the linguistic methodology with the insights gained from a literary approach.
Keywords: phraseology; phraseological unit; collocation; femininity; liberation; independence; transgression